Understanding the response of large South African companies to HIV/AIDS - David Dickinson; Marion Stevens (Taylor & Francis Group, 2005)
This paper provides a framework analysing the response of South African companies to HIV/AIDS. Drawing on three case studies of companies, each with over 20 000 South African-based employees, we identify six 'drivers' that influence corporate behaviour regarding HIV/AIDS: legal requirements, voluntary regulation, business costs, social pressures, visibility of the disease, and individuals within companies. We suggest that costs calculations, while possibly underestimating indirect and macro-implications, are not key in driving company responses to HIV/AIDS. The law and voluntary regulation have influenced, but not determined, the response of companies to HIV/AIDS. Social pressures on companies are of importance, but the scale and complexity of need in South Africa has seen the deflecting of this driver. Of greater reference in determining responses has been the social pressure of other companies' responses. The general visibility of the AIDS epidemic is also a significant factor in explaining companies' responses to HIV/AIDS. Moreover, the visibility of HIV/AIDS within companies has influenced the responses of often relatively weak, internal agents who have been attempting to drive companies' HIV/AIDS programmes.We conclude that external drivers - legal requirements, economic performance, and social pressures - have framed corporate responses to HIV/AIDS to a degree, but have generally been weak. Moreover, there has been relatively little synergy between these external drivers and the internal drivers - voluntary regulation, visibility, and company HIV/AIDS 'champions' - that could propel companies into pro-active, bold responses to HIV/AIDS.